Application of structural integrity assessment procedure on an axle pin of a wind turbine. Issue 8 (August 2017) - Gubeljak, N.; Cvetic, M.; BOŽIĆ, Ž.; Predan, J.
Abstract: The axle pin is one of the most critical components of a wind turbine. Because 2 bearings are mounted on the axle pin, it is not subjected to torque and is designed only to carry bending stresses. The axle is usually made by a casting process, which can induce defects. After casting of the axle pin, radial surface cracks were detected outside by ultrasonic and magnetic particle inspection. The first goal of this paper is to establish defect tolerance in the design of the axle pin, ie, at what critical crack size can we expect failure of the axle pin? The second aim is assessing the remaining lifetime of the defected axle pin used in operation of a wind turbine. Both issues are important to prevent unexpected failure and establish a system for on‐line structural health monitoring. This paper presents a procedure for the structural integrity assessment of axle pins by considering their material properties and fatigue crack growth parameters and comparing them with their fatigue design curve.